Gambaran Nilai Pengukuran Parameter Sefalometrik Pasien Ras Deutro Melayu Usia 6-12 Tahun Menggunakan Analisis Steiner - Tasqia Alifa Syabira; Olivia Piona Sahelangi (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: Cephalometric analysis is an important tool in the field of orthodontics. It is used to examine the growth and development of facial bones in treatment planning, and changes between before and after treatment in evaluation stage. Steiner's analysis uses angle dan distance measurements to determine the patient's skeletal position. Steiner's analysis includes the position and inclination of the incisors to the jaw and the position of the jaw to the cranial base. This study was thus carried out to describe the value of cephalometric parameter measurements of Deutro-Malay race patients aged 6-12 years using Steiner's analysis. Materials and Methods: This study is a descriptive observational method with a cross-sectional study design. Samples were taken from secondary data of cephalogram orthodontic patients RSGM FKG Usakti in 2017-2018. The analysis was carried out by measuring 11 Steiner's analysis parameters, namely: SNA, SNB, SND, ANB, Go-Gn to SN, U1-NA, L1-NB, U1-L1, Occl-SN. Results: Based on Steiner's analysis, the cephalometric mean value of RSGM FKG Usakti orthodontic patients was SNA of 80.80; SNB of 76.60; SND of 72.990; ANB of 4,240; Go-Gn to SN is 36.80; U1-NA is 26,920 and 3,93 mm; L1-NB of 32.10 and 5.98 mm; U1-L1 of 116,890; Occl-SN is 20,680. Conclusions: Malay Deutro Race has a tendency for class II, skeletal class II malocclusion, retrusive symphysis, less developed horizontal growth patterns, and incisive proclination.